2000 Blasting in The New Millennium - A Wake-Up Call for Blasters - Ann Barron (International Society of Explosives Engineers, 2004)
Commercial drivers have new guidelines regarding how long they can stay on the road without taking a break. Transportation officials say the new Hours of Service rule that took effect January 4th will reduce driver fatigue and prevent hundreds of injuroes, thousands of crashes and save the American economy about 628 million dollars a year.